Parental Criticism is an Environmental Influence on Adolescent Somatic Symptoms - Horwitz, BN (J Fam Psychol, 2015)
Previous studies have suggested that parental criticism leads to more somatic symptoms in adolescent children. Yet this research has not assessed the direction of causation or whether genetic and/or environmental influences explain the association between parental criticism and adolescent somatic symptoms. As such, it is impossible to understand the mechanisms that underlie this association. The current study uses the Extended Children of Twins design to examine whether parents’ genes, adolescents’ genes, and/or environmental factors explain the relationship between parental criticism and adolescent somatic symptoms. Participants came from two twin samples, including the Twin and Offspring Study in Sweden (N = 868 pairs of adult twins and each twin’s adolescent child) and from the Twin Study of Child and Adolescent Development (N = 690 pairs of twin children and their parents). Findings showed that environmental influences account for the association between parental criticism and adolescent somatic symptoms. This suggests that parents’ critical behaviors exert a direct environmental effect on somatic symptoms in adolescent children. Results support the use of intervention programs focused on parental criticism to help reduce adolescents’ somatic symptoms.